Statement by the Managing Director on the Work Program of the Executive Board. (Policy Papers; Policy Paper, 2008)
Our work on restructuring the IMF is now well advanced, but our work on refocusing the IMF is only beginning. Over the next few months I expect to see a shift of emphasis in our work away from our internal concerns such as the size and governance structure of the IMF and toward the actions the IMF will take to help our members meet global challenges. Drawing on the ideas set out in my statement on Strategic Directions in the Medium-Term Budget, I will propose action in some of the major areas of the IMF's work. The principle guiding our work will continue to be responsiveness to our members' needs with a focus on the IMF's comparative advantage. We will aim to make substantial progress over the next few months but in a number of areas, the work will continue beyond the Annual Meetings.